Aesthetic Considerations of Space and Reading Culture: A Qualitative Analysis of the Redesign of Literacy Environments on Student Learning Motivation - Muhammad Gufran; Nijam Zahri Najwah; Irsan Kadir; Tanriolle Tanriolle (Pedagogi : Jurnal Pendidikan dan Pembelajaran, 2025)
The cultivation of a robust literacy culture in secondary education is frequently hindered by stagnant, uninspiring physical environments that fail to spark student interest. This study analyses how the aesthetic redecoration of literacy spaces influences students reading motivation and learning engagement at State Junior High School 1 Galesong Selatan. Adopting a qualitative descriptive approach, the Research was conducted over four months, utilizing participatory observation, in-depth interviews with 30 purposively selected students and educators, and extensive documentation to capture participants lived experiences within a transformed aesthetic ecosystem. The results demonstrate that the strategic integration of visual arts including thematic murals, ergonomic furniture arrangements, and the application of color psychology successfully transitioned the literacy room from a sterile facility into an "aesthetic sanctuary." Findings reveal a profound transformation in students' perceptions and behaviors, characterized by a natural inclination toward increased visit frequency, prolonged engagement with reading materials, and heightened institutional pride. The discussion highlights that aesthetics serve as a silent pedagogical agent, lowering affective filters and rebranding reading as a creative social activity rather than a rigid obligation. This study concludes that "Aesthetic Pedagogy" offers an innovative framework for educational reform, emphasizing that physical space is a dynamic participant in the learning process.